Selective ortho-methylation of phenol with methanol over copper manganese mixed-oxide spinel catalysts - Reddy, A. Satyanarayana; Gopinath, Chinnakonda S.; Chilukuri, Satyanarayana V. (Journal of Catalysis, 2006)
Methylation of phenol with methanol as an alkylating agent to produce 2,6-xylenol was investigated over copper manganese mixed oxide spinels, CuxMn3-xO4 (x = 0, 0.25, 0.5, 0.75, and 1) prepared through co-precipitation. The catalytic activity strongly depends on the composition, acid-base properties, and structural stability. Various parameters, including catalyst composition, reaction temperature, feed composition, and durability of the catalyst during methylation, were investigated. Mainly o-cresol and 2,6-xylenol, along with small amounts of mesitol, were found in the product. A high ortho-selectivity of 100%, with 2,6-xylenol selectivity of 74%, was observed over Cu0.25Mn2.75O4 at 673 K. These catalysts were investigated using various techniques, including BET surface area, XRD, DRS UV-vis, TPD of NH3 and CO2, TPR, and X-ray photoemission spectroscopy (XPS). Powder XRD of the catalysts revealed the formation of copper-manganese spinels with hausmannite (Mn3O4) tetragonal structure, for x = 0-0.5, whereas an increase in copper content (x > 0.5) led to the formation of cubic Cu1.5Mn1.5O4 phase. DRS UV-vis, and FTIR further supported the changes in structural phases observed by XRD. Temperature-programmed desorption Of CO2 and NH3 showed that the catalysts have strong basicity along with weak acidity when x = 0 and 0.25. XPS and XAES analysis revealed the presence of only Cu2+ ions in fresh sample with x = 0.25, whereas for x = 1.0, both Cu1+ and Cu2+ were observed. The deactivation of the catalysts is attributed to structural changes occurring during the reaction. Catalytic activity is correlated with structure, as well as with acid-base properties. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: 2; 6-xylenol; acidity-basicity; copper-manganese oxides; ortho-alkylation; phenol methylation; Spinels

Significance of optimal N-doping in mesoporous carbon framework to achieve high specific capacitance - Sahoo, Malaya K.; Gogoi, Pranjal; Rajeshkhanna, G.; Chilukuri, Satyanarayana V.; Rao, G. Ranga (Applied Surface Science, 2017)
Nitrogen-doped mesoporous carbon (NMC) has been synthesized by sol-gel process using a mixture of phenol and formaldehyde as source of carbon, and melamine as source of nitrogen. The Ludox-AS40 (40 wt% SiO2) is employed, for the first time, as hard template to obtain polymeric gel by prolonged heat treatment at 80 degrees C. The wt% of nitrogen is tuned by varying the weight ratio of melamine to phenol. Stable mesoporous carbon frameworks are obtained by pyrolysis of the dry gel at 800 degrees C in nitrogen atmosphere and treated with alkali to remove silica. One of the carbon framework samples has 11 wt% nitrogen doping and shows pore volume of 0.5 cm(3) g(-1) and surface area 609 m(2) g(-1). The other carbon frame work sample has 6 wt% nitrogen doping and shows higher pore volume of 1.1 cm(3) g(-1) and surface area 736 m(2) g(-1). The later sample exhibits highest electrochemical capacitance of 196 F g(-1) at 0.5 A g(-1) while the former shows only 146 F g(-1) at 0.5 A g(-1). However, both the NMC electrodes show good cyclic performance (91% of the initial capacitance after 1000 cycles) in an aqueous KOH electrolyte. This study demonstrates that there is an optimum level of nitrogen doping required to keep the meso-structure of carbon network intact, simultaneously maintaining high surface area and sufficient electrical conductivity for electrochemical applications. (C) 2016 Elsevier B.V. All rights reserved.